'I Need a Cigarette' — The Effects of Cigarette Smoking on Depression and Anxiety of Youth With Early Onset Schizophrenia. Issue 1 (4th July 2016) - Chen, Ya-Ling; Rittner, Barbara; Maguin, Eugene; Dziadaszek, Shannon
Abstract : The aim of this research was to examine effects of cigarette smoking on depression and anxiety among children and adolescents (youth) with early onset schizophrenia and/or psychosis. Data were obtained from the national evaluation of the Comprehensive Community Mental Health Services for Children and Their Families Program (CMHS Program). Cubic mixed models were used to analyze the longitudinal data with seven waves (over 3 years). Results showed that 29% youth ( N = 117, mean age at intake = 13.9) smoked cigarettes in any prior 6-month period. Cigarette users had high levels of initial and sustained depression and anxiety throughout the seven waves. Predicted depression and anxiety scores of cigarette users and non-users showed that cigarette users had higher but more stable states of anxiety and depression. Results suggested that youth with EOS might use cigarettes for mood regulation. Implications of results for psychologists and counsellors in schools are discussed.